Pediatric nondura-based clear cell meningioma of the cauda equina: case report and review of literature. (3rd March 2020) - Kawasaki, Yukari; Uchida, Susumu; Onishi, Kouhei; Okanari, Kazuo; Fujiki, Minoru
Abstract: Although spinal meningiomas are uncommon in children, clear cell meningioma has been described as the most common variant of spinal meningiomas in the pediatric age group. 24 cases of pediatric spinal clear call meningioma have been reported in the literature. We report one case and review the literature regarding pediatric spinal clear cell meningioma.